A Big-book Writing Training through Education for Sustainable Development Approach: A Teacher Competency Development: Pelatihan Penyusunan Bigbooks melalui Pendekatan Education for Sustainable Development: Pengembangan Kompetensi Guru - Tri Mulyati; Wulan Wangi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
In a global context, the role of education is becoming increasingly strategic in line with the demands of achieving the Sustainable Development Goals (SDGs), especially the fourth goal, which emphasizes the importance of inclusive, equitable, and quality education. In line with this, the Education for Sustainable Development (ESD) approach has become a vital instrument in transforming educational practices to make them more relevant to the challenges and needs of the 21st century. The presence of ESD approach facilitates students to learn about how to behave in an enviromental friendly manner and apply sustainable living concept. In conjunction with this issue, the teachers play a very significant role as the main actor in integrating ESD principles in the teaching and learning process. The bigbook writing training was designed to improve technical skills in the media development, and strengthen the teachers’ conceptual knowledge related to the integration of sustainable value in the classroom. Performance-based training was selected as the training method in this activity. The training was conducted for one day and involved 10 teachers at SDN 1 Rejosari. The results of the activity evaluation showed that ≥ 80% of participants gave a postive response to the content and methods of material delivery. ≥ 80% of participants showed a positive perception on the impact and benefits of the program for teachers. The feedback from the participants shows that this training enrich the participants’ knowledge and skills on how to protect the environmen and minimize the climate change through bigbook writing.